Classification Of Breast Lesions Using Artificial Neural Network. - Mashor, M Y; Esugasini, S; Mat Isa, N A; Othman, N H (2006)
This paper presents a study on classification of breast lesions using artificial neural network. Thirteen morphological features have been extracted from breast lesion cells and used as the neural network inputs for the classification.